Upregulation of ICAM-1 Expression on J774.2 Macrophages by Endotoxin Involves Activation of NF-κB but not Protein Tyrosine Kinase: Comparison to Induction of iNOS - Hartmut Ruetten; Christoph Thiemermann; Mauro Perretti (Hindawi Limited, 1999)
This study compares the signal transduction pathway which leads to the upregulation of intercellular adhesion molecule-1 (ICAM-1) expression with that of the increase in the expression of inducible nitric oxide synthase (iNOS) protein and activity caused by endotoxin in cultured J774.2 macrophages. Treatment of J774.2 cells with lipopolysaccharide E. coli (LPS) induced a concentration-dependent increase in the expression of ICAM-1 on the cell surface within 4 h and an increase in iNOS protein and activity at 24 h. The upregulation of ICAM-1 expression on J774.2 macrophages caused by LPS was significantly inhibited by pretreatment of the cells with inhibitors of the activation of the nuclear transcription factor NF-κB, such as L-1-tosylamido-2-phenylethylchloromethyl ketone (TPCK), pyrrolidine dithiocarbamate (PDTC), rotenone or calpain inhibitor I, but not by the tyrosine kinase inhibitors, tyrphostin AG126 or genistein. In contrast, genistein or tyrphostin AG126 also prevented the induction of iNOS protein and activity in J774.2 macrophages elicited by LPS. Thus, the increase in the expression of ICAM-1 on J774.2 macrophages by endotoxin involves the activation of NFκB, but not of protein tyrosine kinase.